PENGARUH KUALITAS PELAYANAN DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING SERTA DAMPAKNYA TERHADAP MINAT MEREFERENSIKAN NASABAH BANK OCBC NISP CABANG CIK DI TIRO YOGYAKARTA - Devinta Kris Amalia Putri (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of quality of service ad product innovation on competitive advantage and interest referenced of Bank OCBC NISP Brach Cik Di Tiro Yogyakarta Costumers.The research was conducted quantitatively by survey method using questionnaire. The sample of this research is the customer who happened to be encountered in PT Bank OCBC NISP Branch Cik Di Tiro Yogyakarta as many as 100 people who have Saving Product Tanda360o Plus and at least 6 months have become customers who have Saving Product Tanda 360o Plus. The sampling technique used purposive sampling technique. Data were analyzed by using multiple linear regression analysis. The result of the analysis showed that service quality variable had a significant and positive influence on competitive advantage. Product Innovation Variable had a significant and positive effect on Competitive Advantage. Service Quality Variables had a significant and positive influence on Referring Interest. Product Innovation Variables had a significant and positive effect on Referring Interest. Variable of Competitive Advantage had a significant and positive influence on Referring Interest. The quality of service, product innovation and competitive advantage had a contributed 70.1% in influencing the interest of referring customers of Bank OCBC NISP.